Rung: Colours of Consciousness - Bhat, Zeenia; Reddy, Vegitha (Tattva journal of philosophy, 2025)
‘Rung,’ colour, has been a subject of exploration by philosophers as the study of consciousness progresses. They believe colours, besides their objective, physical understanding, also have a phenomenal and subjective understanding, for example, the ‘feeling’ that we get when the redness of the red setting sun is felt, or the blueness of the blue sky is experienced. This feeling or subjective phenomenal experience is what has been called consciousness or qualia, qualia being the properties of such experiences. However, deciphering such experiences is what has been the greatest task given to the philosophers; the mystery of this ‘feeling’ or phenomenal experience we get when a colour is perceived is also a mystery, if unfolded, it helps us to decipher what consciousness is. This paper attempts to investigate the subjective experience of colour as explored in Indian Bakhti and Sufi poetry. Colour or ‘rung’ has been extensively used as imagery in such poems, where the experience of being in a divine state is equated to being immersed in the experience of a colour. The divine, also known as ‘rungrez,’ the colour dyer or the colour giver, is the one who infuses us with such colourful experience, the experience of himself or consciousness. In this way, the paper will explore the subjective experiences (of colour) as portrayed in such poetry and will try to perceive the question of consciousness from a different perspective.